Experts and Other Terminology Users as Intended Users of Terminological Dictionaries - Fajfar, Tanja; Žagar Karer, Mojca (Jezikoslovni zapiski, 2018)
This paper identifes various terminology users that deal with terminology from their own perspectives and thus have diﬀerent needs as the intended users of terminological dictionaries. The basic diﬀerence between groups of terminology users is that only experts understand terminology as a set of designations for concepts from a conceptual system of a particular domain. They recognize terminology as designations for specialized content. Other terminology users do not deal with terminology at the conceptual level, but at the expression level. A terminological dictionary and the information contained in it should be adjusted to the intended dictionary users.